THE CRIMINAL CASSATION DEPARTMENT OF THE GOVERNING SENATE AS THE HIGHEST COURT OF THE RUSSIAN EMPIRE IN THE POST-REFORM PERIOD: LEGAL STATUS AND LAW ENFORCEMENT PRACTICE - PARSHINA Natalia Viktorovna (Правовое государство: теория и практика)
The Criminal Cassation Department of the Governing Senate was established as part of the reforms of Alexander II in the 60s of the 19th century as the highest court, which verified the legality of judgements handed down in a case by judicial chambers, district courts and magistrates’ assemblies. The purpose of the study is to analyse the specifics of cassation appeal against sentences in the post-reform period on the basis of normative legal acts of the Russian Empire, sources of judicial practice, archival materials, which are first introduced into the scientific turnover. The methodological basis of the research is a set of general scientific (induction, deduction, analysis, comparison) and specific scientific (historicallegal, formal-legal, comparative-legal) methods of cognition. Results: the author concludes that granting the Governing Senate the right to verify the legitimacy of judicial acts in the course of the reform of 1864, contributed to the resolution of lawful, justified and fair sentences. In general, the institution of cassation acted as a guarantor of the observance by the judicial authorities of the principles enshrined in the Judicial Statutes of 1864.